Da mediação voltada à cidadania às essencialidades da atuação do mediador: a Independência, a Equidistância e o Não-Poder - Nathane Fernandes da Silva (2013)
This dissertation is the study of mediation as a non-adversarial, consensual and dialogical conflict resolution method, especially geared to the promotion of citizenship by those involved in conflict situations, seeking to resolve them through that method. Centered on the figure of the mediator, the purpose of this study was to distinguish three essential but not exclusive requirements related to the role of the mediator focused on promoting the involvement, the accountability and participation of mediandos in the process of solution of their demands: independence, equidistance and non-power. We concentrated on the investigation if the mediator guided by these three essentialities has the necessary tools to conduct a mediation process focused on the promotion of citizenship, taking out of this method a unique character of dispute resolution. To do so, we started with a concept of mediation focused on access to citizenship, going through the importance of the mediator in the mediation process to reach the emphasis of the three essentialities for its operations. Finally, we attempted to illustrate the study carried out with the analysis of two cases of Programa Pólos de Cidadania from Federal University of Minas Gerais, checking if the mediators of those cases worked guided by independence, equidistance and non-power, thus favoring an effective exercise of citizenship by the mediandos involved in the processes analyzed.